(untitled) (International Journal of Ayurveda and Pharma Research, 2016)
Ayurveda is the traditional system of Indian medicine and being historical, linguistic, religious, philosophical importance of Ayurveda, it is very necessary to do critical study of Ayurveda according to ancient Indias history, Prakrita, Pali (Magdhi), Ardhamagdhi languages, religious and philosophical point of view. It is prejudice to compare Ayurveda with the modern science. First, we should try to know what is Ayurveda? It is considered as science of life but what is the meaning of science according to Indian philosophy? Ayurveda is considered as the philosophy as well as clinical science also. The two main distinctions of Indian philosophy – the believer (i.e. Sankhya, Yog, Nyaya, Vaisheshika, Purva Mimansa, Uttar Mimansa) and the atheist (i.e. Charvaka, Jain and Baudha) philosophy. Unless and until we have the deep knowledge of Indian philosophical sciences i.e. Darshan Shastras (Aastika and Naastika), we wont be able to understand Ayurveda properly. Therefore, it is the need of time to do critical study of Darshan Shastras (Aastika and Naastika) and it is to be noted that with the help of Sanskrita language alone we wont be able to achieve our goal; it is very much important to have the knowledge of languages such as Prakrit, Pali which is also known as Magadhi and Ardhamagdhi, then only we could be able to understand the proper meanings of Darshan Shastras (Aastika and Naastika); Buddhist literature is available in the Pali language which is also known as Magdhi; it was the dialect of ancient north India, and Ardhamagdhi is the language in which Jain literature is available. This research paper is an attempt to review the Ayurveda literature regarding historical facts and what are the means so that we could able to understand Ayurveda appropriately.